2009
DOI: 10.1093/ntr/ntp042
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with varenicline and nicotine replacement therapy

Abstract: Our findings suggest that combination therapy with varenicline and NRT is safe and well tolerated among patients in a residential tobacco treatment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
2
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 15 publications
0
44
2
2
Order By: Relevance
“…We combine NRT in the form of nicotine patches to help patients during the initial phase of titrating the dose of varenicline. A similar approach has been used in a residential smoking cessation program elsewhere [20]. Should patients have any contraindication to varenicline, then bupropion (for 12 weeks, titrated from 150 mg per day for 3 days, then increased to 300 mg per day) and NRT are used.…”
Section: Methodsmentioning
confidence: 99%
“…We combine NRT in the form of nicotine patches to help patients during the initial phase of titrating the dose of varenicline. A similar approach has been used in a residential smoking cessation program elsewhere [20]. Should patients have any contraindication to varenicline, then bupropion (for 12 weeks, titrated from 150 mg per day for 3 days, then increased to 300 mg per day) and NRT are used.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to first-line pharmacologic management, smokers are started on the indicated dose of varenicline (0.5mg daily during days 1-3, to 0.5mg twice a day during days 4-7, 1.0mg twice a day until the end of treatment) or bupropion (150mg daily during days 1-3, followed by 150mg twice a day until the end of treatment), in combination with nicotine replacement therapy (nicotine patches and nicotine lozenges or gum -NRT is prescribed at an initially high dose proportional to the number of cigarettes smoked by the patient, and titrated down towards the end of treatment). NRTs are combined with oral agents (varenicline or bupropion) to help patients during the initial phase of up-titrating the dose of either oral agent, and to control acute urges and withdrawal symptoms that may continue to occur in the first few weeks of therapy after completely quitting [with regards to varenicline and NRT in particular, a similar approach has been used in a residential smoking cessation program elsewhere (Ebbert et al, 2009)]. The choice between varenicline and bupropion is determined by clinical factors such as existence of contraindications to either drug, and the presence of comorbidities (e.g.…”
Section: Settingsmentioning
confidence: 99%
“…Recently, investigators have evaluated the combination of varenicline, the newest cessation medication, with other therapies. Ebbert et al [37] reported a case series of smokers who used varenicline plus NRT (n=104) compared with usual care smokers who were treated prior to the release of varenicline (n=135). They found that the combination of varenicline with NRT was safe and well-tolerated in a residential tobacco treatment program [37].…”
Section: Advances In Pharmacotherapymentioning
confidence: 99%